Prenatal diagnosis of a de novo pathogenic HNRNPK variant in a Chinese fetus with abnormal ultrasound soft markers: a case report - Zhu, Yuying; Yang, Zhen; Zhu, Qiumin; Wu, Ke; He, Junying; Zhou, Hongmei (Frontiers in Genetics, 2025)
BackgroundHeterozygous pathogenic variants in HNRNPK cause Au-Kline syndrome (AUKS), a neurodevelopmental disorder characterized by congenital anomalies and developmental delay. Prenatal diagnosis of AUKS remains challenging due to nonspecific ultrasound findings, such as increased nuchal translucency (NT) and nuchal fold (NF), which overlap with other genetic conditions.MethodsWhole-exome sequencing (WES) was performed on a fetus exhibiting increased NT and NF thickening, alongside parental samples. Identified variants were validated by Sanger sequencing, with structural and functional impacts predicted using bioinformatic tools.ResultsWES revealed a de novo heterozygous frameshift variant in HNRNPK (NM_031263.4: c.504_507del) in exon nine of 17, which has been deposited in the ClinVar database with accession number VCV003899365 and classified as pathogenic (P). This variant results in a truncated protein (p.Lys168AsnfsTer35): bioinformatic predictions indicate the resulting mRNA is likely subject to nonsense-mediated mRNA decay (NMD), and any escaping mRNA would produce a severely truncated protein lacking critical functional domains, rendering it nonfunctional. Sanger sequencing confirmed the variant was absent in both parental genomes. Ultrasound findings aligned with AUKS-associated nonspecific prenatal anomalies, and post-induction gross examination confirmed subtle AUKS-related craniofacial features, expanding the known prenatal phenotype of AUKS and providing phenotypic severity context.ConclusionStructural and functional analyses provide mechanistic insights into the variant’s pathogenicity, highlighting HNRNPK’s role in fetal development. These findings advocate for integrating genomic and phenotypic data to improve prenatal diagnosis of rare genetic syndromes.